Nurses' Work Motivation in Providing Nursing Care During the COVID-19 Pandemic - Sekani Niriyah; Yecy Anggreny (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the performance of nurses during the COVID-19 pandemic in providing nursing care to achieve goals in meeting the needs and independence of patients. The research method used is quantitative research with a descriptive survey design. The results showed that the majority of respondents were female, as many as 57 people (79.2%), the last education was D3 nursing, as many as 26 people (36.1%), the average age was 34.5 years with the lowest age of 23 years and the highest was 47 years, the average length of work was 9.03 years with the lowest tenure was two years and the highest was 22 years, and intense work motivation as many as 40 people (55.6%). In conclusion, the explanation of nurses in providing nursing care during the COVID-19 pandemic is in the low category. Keywords: Nursing Care, Work Motivation, COVID-19 Pandemic